Morpho-physiological and molecular characterization of upland rice genotypes for blast disease resistance - Khatun, Tuhina (2016)
Upland rice is a valuable base population for protecting against genetic erosion and broadening the gene pool of rice germplasm. Blast caused by the fungus Magnaporthe oryzae is the most impactful rice disease, and it can be severe in upland/dry land cultures. This study aimed to identify and characterize upland rice germplasm for blast disease resistance. Initially, 50 upland rice genotypes, including one resistant check, Pongsu Seribu-1, and one susceptible check, MR219, were evaluated to identify new sources of resistance and assess diversity based on reactions to M. oryzae. Resistant reactions were observed in the genotypes Biaw Bood Pae, Blau Noc, Chirikata 2, IPPA, IR 5533-50-1-10, IR 5533-55-1- 11, Ja Hau, Ja No Naq, BR26, BRRI dhan42 and BRRI dhan43. The 50 genotypes were grouped into five clusters based on the greater similarities of their reactions to the blast fungus. The morphological, physiological and yield trait characteristics of 27 globally diverse blast-resistant genotypes were further evaluated. Additionally, the genotypes were analyzed to determine the correlations between and diversity among these characteristics. The BRRI dhan43, C, Choke Tang and Chirikata 2 were identified as early-maturing genotypes that provided the best yields. The largest heritability coupled with a high genetic advancement was recorded for a number of filled grains/panicle and yield/plant, demonstrating that these traits can be successfully transferred to offspring if selection of these characteristics is performed via a hybridization program. The 27 genotypes were grouped into six clusters based on the contributing morphological, physiological and yield characteristics. The blastresistant, early-maturing, high-yield genotype BRRI dhan43 was then finally characterized to determine the molecular mechanism underlying the plant-microbe interaction using next generation sequencing (NGS). The reference-based alignment produced total reads of 66.9 and 66.2 million in the uninoculated and inoculated plant samples, respectively. This study showed a large number of SNPs with the value of more than 95 and 88 thousand for healthy and diseased samples, respectively. A total of 2,733 differentially expressed genes (DEGs) were identified from Oryza sativa cv BRRI dhan43 and M. oryzae race P7.2 interactions, of which 43% up-regulated and 57% down-regulated, About 9.9% of genes involved in incompatible interaction between BRRI dhan43 and fungus race P7.2 pathosystem. The resistant cultivar, BRRI dhan43 responded upon colonization of virulent fungus P7.2, inducing both pathogen-associated molecular pattern (PAMP)-triggered immunity (PTI) and effector-triggered immunity (ETI). Although the functions yet to be known, based on the results of transcriptome analysis, two novel race-specific elicitors AVR4 and AVR9 in virulent race P7.2, and three resistant proteins MLA10, L6 and RPS in rice cultivar BRRI dhan43 were reported for the first time during host-pathogen interaction.